Solvent effects and photocatalytic activity in the simple, template-free solvothermal synthesis of Cu2O - Abdussamad Mukhtar Mohammed; Mustapha Usman Nasir (Next Materials, 2025)
Copper(I) oxide is an interesting p-type semiconductor photocatalyst with tremendous properties and rapid photocatalytic activity. It has various methods of synthesis, however, most of the Cu2O produced using those methods are prone to instability by undergoing rapid change of phase to CuO. As such, there is an urgent need for a facile, economical, and safe method of synthesis of Cu2O. A solvothermal method is one of the most efficient, low-cost, and facile method of synthesis of nanoparticles, however, the shape, morphology, and size of the particles synthesized using the solvothermal method are dependent upon the type of solvent and reducing agents used, as such the choice of a suitable solvent and reducing agent is the first step for a successful synthesis. In this work, a simple and template-free solvothermal method was used to prepare Cu2O by utilizing three solvents that act as both solvents and reducing agents for the first time to explore the impact of different solvents in the solvothermal synthesis of Cu2O. The solvents were used without the presence of any surfactant or capping agent, which is rarely reported. They include absolute ethanol, ethylene glycol, and glycerol. The structural, physical, and photocatalytic activity studies of all the synthesized samples exhibited superior properties of the Cu2O produced using absolute ethanol. This reveals the reducing capability and potential of absolute ethanol in solvothermal synthesis. Extensive discussion was done on the effects of solvents on the solvothermal synthesis of Cu2O along with the mechanism of the degradation of congo red dye on the surface of Cu2O photocatalyst. Although the solvothermal method is a commonly published methodology for synthesizing different nanoparticles, no research has been conducted to explicitly examine the effect of various solvents on the solvothermal synthesis of Cu2O. As such, this research will undoubtedly contribute to the field of material science and understanding of how solvent properties like redox, polarity, complexation, viscosity, and surface tension affect the properties of the final product synthesized using solvothermal methods.